Young ethnic minority men and their movement into gang related street communities - a question of preventing feelings of social alienation - Kirsten Elisa Petersen (Social Work & Society, 2019)
In what ways are young men's movement into and affiliation to gang related street communities associated to feelings of social alienation? This article analyses this question based on semi-structured research interviews with six young ethnic minority men, all associated with gang related street communities. Based on Safipour et al.'s concept of social alienation described as a sense of not belonging or feelings of exclusion, the article explores how the young men's everyday life in the ghettos and in school shows experiences of exclusion from social communities and a sense of not belonging. The concept of everyday life relates to Holzkamp's concept of the conduct of everyday life reflected as participation and human actions in specific social contexts.The concept of participation draws the attention to how children and young people develop and learn through their participation in communities, while Mehan et al.'s concept of social skills in the school's hidden curriculum reveals understandings of difficulties associated with engaging in participation in the school community. Based on this perspective analyzes of the article point to how the young men's everyday life in ghetto areas and school difficulties can lead to movements into gang related street communities that counteract feelings of social alienation.